Analysis of Total Flavonoid Content in Local Kalimantan Plants and Antioxidant Activity: A Review - Nabilla Faoziyyah Azizah; Wildan Hidayah; Risa Dwi Apriani; Dia Septiani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Flavonoids are one of the largest groups of compounds in the natural phenol group that are widely found in all types of green plants, so they are almost always found in every analysis of plant extracts. Meanwhile, antioxidants are inhibitors used to inhibit the autooxidation process. Flavonoids have the ability to act as antioxidants because they can transfer electrons, so they can neutralize free radicals. This review identifies the levels of flavonoids and antioxidant activity of local Kalimantan plants, utilizing half-maximal inhibitory concentration (IC50) values as a standardized quantitative parameter for assessing antioxidant potency and identifying promising sources of natural antioxidants. The maceration extraction method with ethanol at concentrations of 70% and 96% was used to obtain active compounds, and antioxidant activity was assessed using the DPPH method. The results showed that several species, such as Bajakah Kalalawit (Uncaria cordata) and Karamunting (Rhodomyrtus tomentosa), had very low IC50 values, namely 9.159 ppm and 14.06 μg/mL, indicating very strong antioxidant activity. Thus, local Kalimantan plants have great potential as a source of natural antioxidants and could be developed as raw materials for antioxidant-based health products. The findings of this review offer comprehensive evidence to guide future research, standardization, and commercialization of indigenous Kalimantan plants for the development of effective and sustainable natural antioxidant products.